Prevalence of Thoracic Aortic Aneurysms in Patients with Degenerative Abdominal Aortic Aneurysms: Results from the Prospective ACTA Study. (June 2021) - Gaudry, Marine; Barral, Pierre-Antoine; Blanchard, Arnaud; Palazzolo, Sylvie; Bolomey, Sonia; Omnes, Virgile; De Masi, Mariangela; Carcopino-Tusoli, Magali; Meyrignac, Olivier; Rousseau, Hervé; Jacquier, Alexis; Hassen-Khodja, Reda; et al.
Abstract : Objective: There are no recommendations for screening for thoracic aortic aneurysms (TAAs), even in patients with infrarenal abdominal aortic aneurysms (AAAs). The aims of this study were to determine the prevalence of TAAs in patients with AAAs and to analyse the risk factors for this association. Methods: This was a multicentre prospective study. The Aortic Concomitant Thoracic and Abdominal Aneurysm (ACTA) study included 331 patients with infrarenal AAAs > 40 mm between September 2012 and May 2016. These patients were prospectively enrolled in three French academic hospitals. Results: Patients were classified as having a normal, aneurysmal, or ectatic (non-normal, non-aneurysmal) thoracic aorta according to their maximum aortic diameter indexed by sex, age, and body surface area. Thoracic aortic ectasia (TAE) was defined as above or equal to the 90th percentile of normal aortic diameters according to gender and body surface area. Descending TAA was defined as ≥ 150% of the mean normal value, and ascending TAA as > 47 mm in men and 42 mm in women; 7.6% ( n  = 25) had either an ascending (seven cases; 2.2%) or descending aortic TAA (18 cases; 5.4%), and 54.6% ( n  = 181) had a TAE. Among the 25 patients with TAAs, five required surgery; two patients had TAAs related to penetrating aortic ulcers < 60 mm in diameter, and three had a TAA > 60 mm. In the multinomial regression analysis, atrial fibrillation (AF) (odds ratio [OR] 11.36, 95% confidence interval [CI] 2.18 – 59.13; p  = .004) and mild aortic valvulopathy (OR 2.89, 1.04–8.05; p  = .042) were independent factors associated with TAAs. Age (OR 1.06, CI 1.02 – 1.09; p  = .003) and AF (OR 4.36, 1.21 – 15.61; p  = .024) were independently associated with ectasia. Conclusion: This study confirmed that TAAs coexisting with AAAs are not rare, and one fifth of these TAAs are treated surgically. Systematic screening by imaging the whole aorta in patients with AAAs is clinically relevant and should lead to an effective prevention policy. Graphical abstract: Image 1